ДУХОВНО-НРАВСТВЕННЫЕ АСПЕКТЫ ТЕХНОЛОГИЧЕСКОГО ОБРАЗОВАНИЯ - Шумейко, Т.С. (My University, 2019)
Аннотация В статье рассмотрены возможности духовно-нравственного воспитания через техноло- гическое образование в соответствии с образовательными традициями и основными приори- тетами года молодежи; представлен опыт духовно-нравственного воспитания школьников в проектной деятельности по технологии. Abstract The article deals with the possibilities of spiritual and moral education through technological education in accordance with the educational traditions and the main priorities of the year of the youth. The experience of spiritual and moral education of schoolchildren in the project activity on technology is presented in the article.
Spiritual and moral aspects of technological education
Keywords: духовно-нравственное воспитание; духовность; нравственность; технологическое образование; народный орнамент; народный костюм; проектная деятельность; spiritual and moral education; spirituality; morality; technological education; folk ornament; folk costume; project activities